Geochronology and petrology of Late Cretaceous subduction-related volcanics from Elazig, SE Turkiye: Insights into deciphering petrogenesis and magma generation processes - Erturk, Mehmet Ali (Elsevier Gmbh, 2025)
Subduction-related magmatism, representing the arc setting active just before the collision of the Arabian and Anatolian plates, crops out in large areas in the Southeastern Anatolian Orogenic Belt (SAOB). This study provides new geochemical and geochronological data that may provide important evidence for a more comprehensive understanding of the Late Cretaceous magmatism and evolution processes in the region. The trace element behaviour of igneous rocks bears traces of an N-MORB-like mantle source. The values of Sr-87/Sr-86((i)) range from 0.705250 to 0.706114, Nd-143/Nd-144((i)) from 0.512834 to 0.512888, and epsilon(Nd)(t) from 5.9 to 7.0. Zircon UPb dating indicates that the crystallisation age of the volcanism is 83.93 +/- 1.21 Ma. Energy-constrained assimilation-fractional crystallisation (EC-AFC) modelling confirms that the studied rocks are contaminated by the lower crust to a quite low degree, between similar to 0.1 and 0.4 %. The volcanics were produced from a spinel lherzolite source, with low-medium degree partial melting (similar to 1-12 %). According to the mixing calculation modelling, slab-derived components were involved by approximately 1-4 wt% in magma generation. The estimated mantle melting temperature and pressure conditions from the composition of volcanic rocks were between 1322 and 1442 degrees C and 1.07-2.14 GPa, respectively. The geochronological and geochemical constraints suggest that the possible sources and evolution of the subduction-related volcanics (SRV) record tectonic processes in an intra-oceanic arc setting in response to northward subduction during the Late Cretaceous.
Keywords: Subduction-related volcanics; U-Pb geochronology; Sr-Nd isotope; N-MORB; Eastern Turkiye